Usefulness of B-type Natriuretic Peptides to Predict Cardiovascular Events in Women (From the Women’s Health Study) - Everett, Brendan M. (Am J Cardiol, 2015)
Natriuretic peptides are positively associated with incident cardiovascular disease (CVD), but data in women, particularly with regard to improvements in risk prediction, are sparse. We measured the N-terminal prohormone form of B-type natriuretic peptide (NT-proBNP) in 480 cases of incident CVD (myocardial infarction, stroke, and cardiovascular death) and a reference subcohort of 564 women from the Women’s Health Study who were followed for a median (IQR) of 11.5 (7.3–13.4) years. Median (IQR) NT-proBNP concentrations were higher in women who developed CVD [81 ng/L (50–147)] than those who did not [64 ng/L (38–117); P<0.0001]. For women in the highest as compared to the lowest quartile of NT-proBNP the risk of CVD was 65% higher after adjusting for established cardiovascular risk factors and kidney function (adjusted hazard ratio (aHR) 1.65, 95% CI 1.03-2.64, P-trend=0.03). When analyzed as a continuous variable, the aHR per 1-SD difference in Ln(NT-proBNP) was 1.22 (1.03–1.44; P=0.02). The per 1-SD change in Ln(NT-proBNP) appeared stronger for cardiovascular death (aHR 1.43, 95% CI 1.05–1.94, P=0.02) and stroke (aHR 1.24, 95% CI 1.03–1.50, P=0.03) than for myocardial infarction (aHR 1.09, 95% CI 0.87–1.37, P=0.44). When added to traditional risk covariables, NT-proBNP did not significantly improve the c-statistic (0.751 to 0.757; P=0.09), or net reclassification into <5%, 5 to <7.5%, and ≥7.5% 10-year CVD risk categories (0.014; p=0.18). In conclusion, in this prospective study of initially healthy women, NT-proBNP concentrations showed statistically significant association with incident CVD that was independent of traditional cardiovascular risk factors, but did not substantially improve measures of CVD risk prediction in this sample.